COVID-19, Shincheonji, and the limits of South Korean secularism: The Devil in Patient 31. Issue 3 (27th May 2022) - Cheung, Kin; Noh, Minjung
ABSTRACT: International headlines present the Shincheonji Church of Jesus the Temple of the Tabernacle of the Testimony on the one hand as a 'dangerous sect' or 'cult' and on the other hand as a marginalised Christian group in need of defence by human rights advocates fighting for religious freedom. Our contribution examines the Church's internal text messages and recorded meetings of executives leaked to the press, court orders, arrest orders and charges against its founder Lee Man-hee, and Korean and Anglophone popular media coverage in order to provide a discourse analysis on the political nature of constructing Shincheonji as 'bad' or 'good' religion. We argue that understanding the contemporary situation requires a look at the political history of Protestant Christian – specifically American Protestant – influence on the secularism of South Korea. The state's attempt to enforce public health measures during the COVID-19 pandemic continues to clash with Shincheonji's secret proselytisation process. Protestant influence on the South Korean state is also present in public health values, which are now presented as secular values but have roots in religious traditions. What is at stake here is how state power to immunise and quarantine rationalises and legitimates itself by claiming to protect the majority, at the expense of (religious) minorities.